1990
DOI: 10.1002/bms.1200190804
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and tandem mass spectrometric analyses of deuterium-labeled cysteine-containing leukotrienes

Abstract: Leukotrienes (LT) C4, E4 and N-acetyl-E4, their respective monomethyl esters and 14,15-2H2 analogs have been synthesized. The collisionally activated decompositions of the [M + H]+ and [M - H]- ions formed by fast atom bombardment (FAB) have been studied by tandem mass spectrometry using a hybrid sector/quadrupole instrument. Structurally informative product ion spectra were obtained for each analyte; the fragmentation pathways proposed are consistent with the parallel data obtained for labeled and derivatized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Thus, in spleen and liver almost all of the metabolism of LTC 4 appears to result from this enzyme activity rather than from GGT. 4 , LTD 4 , and LTE 4 from reactions run with homogenates from both wild type and GGT-deficient mice were analyzed by a FAB-MS/MS (20,21). Our studies revealed that the presumed LTC 4 , LTD 4 , and LTE 4 peaks produced the same [M ϩ H] ϩ ions and fragment ions as standard LTC 4 , LTD 4 , and LTE 4 (results not shown).…”
Section: Cleavage Of Substrates Used To Assay Ggt By Ggt-deficientmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, in spleen and liver almost all of the metabolism of LTC 4 appears to result from this enzyme activity rather than from GGT. 4 , LTD 4 , and LTE 4 from reactions run with homogenates from both wild type and GGT-deficient mice were analyzed by a FAB-MS/MS (20,21). Our studies revealed that the presumed LTC 4 , LTD 4 , and LTE 4 peaks produced the same [M ϩ H] ϩ ions and fragment ions as standard LTC 4 , LTD 4 , and LTE 4 (results not shown).…”
Section: Cleavage Of Substrates Used To Assay Ggt By Ggt-deficientmentioning
confidence: 82%
“…Tandem mass spectrometric analyses were performed using a VG ZAB-SEQ (VG Analytical, Manchester, UK) hybrid mass spectrometer of BEqQ configuration (B, magnetic sector; E, electric sector; q, radio frequency-only quadrupole; Q, quadrupole mass filter), equipped with a VG 11-250J data system. The methods employed were similar to those previously described (20,21). Briefly, ionization was accomplished by continuous flow FAB using xenon atoms (8 keV) for the primary atom beam.…”
Section: Methodsmentioning
confidence: 99%
“…The low-energy CID spectrum displayed in Figure 2a was generated in the linear ion trap instrument from protonated LTC 4 [14,16,25]. Scheme 1a shows the fragmentation pattern of these familiar ions.…”
Section: Protonated Ltc 4 (5 6) Isomermentioning
confidence: 99%
“…The product ion spectrum of LTC 4 ( Fig. 2A) is characterized mainly by fragment ions originating from the glutathione part of the molecule (22). All major fragment ions observed in this product ion spectrum at m/z 128, 143, 179, 210, 254, and 272 are also found with similar relative abundance in the corresponding spectra obtained from the samples of the patients (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…To confirm the identification of this signal as LTC 4 , a precursor ion scan for m/z 272 was performed, and the resulting spectra showed the ion at m/z 624 as the most abundant signal. The precursor ion scan for m/z 272 was selected because this fragment has been reported as an abundant fragment ion of LTC 4 generated by fission of the sulfur bridge, with retention of the sulfur atom at the fatty acid part and charge retention at the glutathionyl part, using fast atom bombardment (22) or electrospray ionization (23), as indicated in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%